Understanding the Performance of Organic Photovoltaics under Indoor and Outdoor Conditions: Effects of Chlorination of Donor Polymers - Je, Hwan-Il; Shin, Eul-Yong; Lee, Keun Jun; Ahn, Hyungju; Park, Sungmin; Im, Sang Hyuk; Kim, Yun-Hi; Son, Hae Jung; Kwon, Soon-Ki (American Chemical Society, 2020)
Understanding the effects of the chemical structures of donor polymers on the photovoltaic properties of their corresponding organic photovoltaic (OPV) devices under various light-intensity conditions is important for improving the performance of these devices. We synthesized a series of copolymers based on poly[(2,6-(4,8-bis(5-(2-thioethylhexyl)thiophen-2-yl)benzo[1,2-b:4,5-b']dithiophene))-alt-(5,5-(1',3'-di-2-thienyl-5',7'-bis(2-ethylhexyl)benzo[1',2'-c:4',5'-c']dithiophene-4,8-dione))] (PBDB-TS) and studied the effects of chlorine substitution of its thiophene-substituted benzodithiophene (BDT-Th) unit on its photovoltaic properties. Chlorination of the polymer resulted in a bulk heterojunction (BHJ) morphology optimized for efficient charge transport with suppressed leakage current and an increased open-circuit voltage of the OPV device; this optimization led to a remarkable enhancement of the OPV device's power conversion efficiency (PCE) not only under the condition of 1 sun illumination but also under a low light intensity mimicking indoor light; the PCE increased from 8.7% for PBDB-TS to similar to 13% for the chlorinated polymers, PBDB-TS-3Cl, and PBDB-TS-4Cl under the 1 sun illumination condition and from 5.3% for PBDB-TS to 21.7% for PBDB-TS-4Cl under 500 lx fluorescence illuminance. Interestingly, although the OPV PCEs under 1 sun illumination were independent of the position of chlorine substitution onto the polymer, PBDB-TS-4Cl exhibited better performance under simulated indoor light than its derivative PBDB-TS-3Cl. Our results demonstrate that efficient light absorption and charge-carrier generation play key roles in achieving high OPV efficiency under low-light-intensity conditions.
Keywords: SOLAR-CELLS; GENERATION; GAP